Hubungan Usia, Jenis Kelamin, dan Riwayat Keluarga Dengan Kejadian Hipertensi Pada Lansia di Puskesmas Talang Ratu Palembang Tahun 2023 - Abu Bakar Sidik (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Hypertension is an increase in blood pressure where systolic 140 mmHg and diastolic 90 mmHg. The purpose of the study was to find out what factors were associated with the incidence of hypertension in the elderly at the Talang Ratu Health Center, Palembang City in 2021. The design of this research is cross sectional. The sampling method istechnique purposive sampling. The research subjects were determined by purposive sampling, namely patients who were treated at the Talang Ratu Health Center in 2022. Each research sample is 95 respondents. This research was conducted in June 2023. The data collection used a questionnaire. The results of the analysis oftest Chi-Square showed no significant correlation (P <0.05) for the variable age and family history of hypertension.Â From this research, it is hoped that the Puskesmas will maximize programs related to the elderly such as the elderly posyandu, considering that the elderly are a group at risk for disease.Â